Evaluación de un modelo analítico para la inyección de polímeros como método de recobro mejorado en un área piloto del campo Castilla (2018)
The present work describes the development of an analytical model for the injection of polymers in Campo Castilla. For the elaboration of this model, the properties of the deposit and their respective geological characteristics were taken into account, which affected the phenomena of the rock-fluid interactions and the different secondary and tertiary recovery techniques. For the development of the project, the detailed description of predictive models for polymer injection, CFPM, predictive model for polymer injection and water, PF "and" Predictive model for polymer injection, PFPM ", as well as modifications to analytical models For the injection of water, which could be used to make predictions in chemical injection processes, we chose to use the Buckley-Leverett model with modifications of the Craig, Geffen and Morse Method, for the execution of the project.